2018
DOI: 10.1001/jamadermatol.2018.2352
|View full text |Cite
|
Sign up to set email alerts
|

Association of Bullous Pemphigoid With Dipeptidyl-Peptidase 4 Inhibitors in Patients With Diabetes

Abstract: The association of bullous pemphigoid (BP) with the use of dipeptidylpeptidase 4 (DPP-4) inhibitors among patients with diabetes has recently emerged. The risk of developing BP during treatment with new DPP-4 inhibitor agents like linagliptin is yet to be established. The clinical features and the prognostic outcomes of patients with DPP-4 inhibitor-associated BP are yet to be established. OBJECTIVES Primarily to estimate the association between DPP-4 inhibitor exposure and the development of BP, and secondari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
210
10
12

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(252 citation statements)
references
References 38 publications
20
210
10
12
Order By: Relevance
“…Likewise, a similar increase was also observed in a Japanese pharmacovigilance database, particularly among patients treated with vildagliptin, linagliptin, or teneligliptin (Arai, Shirakawa, Konishi, Sagawa, & Terauchi, 2018). Several observational studies (all case-control designs) have also been conducted and it was reported that a significantly increased or a trend towards an increased risk of BP is associated with the usage of DPP4is with odds ratios ranging between 1.58 and 3.16 (Benzaquen et al, 2018;Kridin & Bergman, 2018;Lee, Lee, Yoon, & Kim, 2019;Plaquevent, et al, 2019;Varpuluoma et al, 2018). Moreover, Benzaquen et al has reported that application of DPP4is increases the risk of BP of almost 3-fold, and the increase is associated with vildagliptin rather than other gliptins (Benzaquen et al, 2018).…”
Section: Dpp4/cd26 Inhibition and Bpsupporting
confidence: 59%
See 2 more Smart Citations
“…Likewise, a similar increase was also observed in a Japanese pharmacovigilance database, particularly among patients treated with vildagliptin, linagliptin, or teneligliptin (Arai, Shirakawa, Konishi, Sagawa, & Terauchi, 2018). Several observational studies (all case-control designs) have also been conducted and it was reported that a significantly increased or a trend towards an increased risk of BP is associated with the usage of DPP4is with odds ratios ranging between 1.58 and 3.16 (Benzaquen et al, 2018;Kridin & Bergman, 2018;Lee, Lee, Yoon, & Kim, 2019;Plaquevent, et al, 2019;Varpuluoma et al, 2018). Moreover, Benzaquen et al has reported that application of DPP4is increases the risk of BP of almost 3-fold, and the increase is associated with vildagliptin rather than other gliptins (Benzaquen et al, 2018).…”
Section: Dpp4/cd26 Inhibition and Bpsupporting
confidence: 59%
“…Increased risk in T2DM patients (Aouidad et al, 2013;Arai et al, 2018;Bene, et al, 2016;Benzaquen et al, 2018;Douros et al, 2019;Garcia et al, 2016;Kridin & Bergman, 2018;Lee et al, 2019;Plaquevent, et al, 2019;Varpuluoma et al, 2018) Taken together, these existing studies fail to strongly support the clinical application of DPP4is in either glucose control or β cell preservation in T1DM patients. The contrary conclusions obtained from the above clinic trials may be attributed to different baseline characteristics of the included patients (such as c-peptide levels, HbA1c, and disease duration), distinct follow-up lengths, different sample size, and other variables.…”
Section: Bpmentioning
confidence: 99%
See 1 more Smart Citation
“…Kridin and colleagues conducted a retrospective case–control study amongst patients with diabetes in a tertiary referral centre for autoimmune bullous diseases in northern Israel. 82 BP cases were age‐ and gender‐matched with 328 controls.…”
Section: Resultsmentioning
confidence: 99%
“…The results of this large population‐based cohort study revealed that the use of DPP‐4 inhibitors was significantly related to an increased risk of BP with an aHR of 2.382 ( P = 0.017). The previous studies have elucidated the association between DPP‐4 inhibitors and BP . In 2019, a large population‐based cohort study of 8569 DPP‐4 inhibitor users and 160 205 non‐DPP‐4 inhibitor users was published by using the UK Clinical Practice Research Datalink .…”
Section: Discussionmentioning
confidence: 99%